TYPES OF PLANTS AS TRADITIONAL MEDICINE IN THE PANTE BAHAGIA SETTLEMENT COMMUNITY IN PAYA BAKONG SUB-DISTRICT, NORT ACEH REGENCY - Yusnidar Yusnidar; Cut Nurmaliah; Hasanuddin Hasanunddin; Djufri Djufri; Wiwit Artika (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
This study aims to investigate the types of plants as traditional medicine in the Pante Bahagia settlement community in Paya Bakong District, North Aceh.. A survey was used as the research method for this study. Respondents in this study were physicians, community leaders, traditional elders, and the general public aged ≥50 years. Data collection was conducted from May 2019 to June 2019. The data collection technique was done observation and interview. Data obtained from interviews with respondents directly in the field, was analyzed descriptively. The results showed that there were 75 types of medicinal plants consisting of 32 families, those have been plants used by the Paya Bakong District community as medicines.Keywords: Plant Type, Medicine, TraditionalPenelitian ini bertujuan mengetahui jenis-jenis tumbuhan sebagai obat tradisional pada masyarakat Kemukiman Pante Bahagia Kecamatan Paya Bakong Aceh Utara. Metode penelitian ini menggunakan metode survei. Responden dalam penelitian ini adalah tabib, tokoh masyarakat, tetua adat, dan masyarakat umum yang berusia ≥50 tahun. Pengambilan data dilakukan pada bulan Mei 2019 sampai dengan Juni 2019. Teknik pengambilan data adalah dengan teknik observasi dan wawancara. Data yang diperoleh dari hasil wawancara dengan responden secara langsung dilapangan, dianalisis secara deskriptif. Hasil penelitian menunjukkan terdapat 75 jenis tumbuhan obat yang terdiri dari 32 familia yang digunakan oleh masyarakat Kemukiman Pante Bahagia Kecamatan Paya Bakong sebagai obat-obatan.Kata Kunci: Jenis Tumbuhan, Obat, Tradisional